Heat shock decrease Saccharomyces cerevisiae UE-ME3 survival exposed to nanoparticles of titanium dioxide. - Capela-Pires, JM (2011)
The main objective of this study was to evaluate the effect of temperature in Saccharomyces cerevisiae exposed to nanoparticles of titanium dioxide (NP-TiO2), because there are scarces studies to evaluate the toxic effects of NP-TiO2 in eukaryote cells. S. cerevisiae UE-ME3, wild-type yeast, belonging to the Enology laboratory collection of University of Evora